Pengaruh Ekstrak Ikan Gabus (Channa striata) dan Metformin Terhadap Kontrol Glikemik Tikus Model Diabetes Melitus - OK Yulizal; Ravinder Singh; Hendra Salim; Hendy Million (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction; Diabetes mellitus (DM) is still a major problem where people with DM today range from 463 million adults aged 20-79 years (9.3%). Cork fish (Channa striata) is one of the natural ingredients containing albumin that is reviewed to have antioxidant activity in beta-pancreatic cells so it is believed to treat DM. Snakehead fish has some efficacy including; has antinociceptive activity, accelerates wound healing, and is an anti-inflammatory. Objective; To determine the effect of snakehead fish extract and metformin on glycemic control of male rats with diabetes mellitus. Methods; This study used an experimental method with a post-test-only control group design. Results; Based on the Kruskal Walis test, it showed (p < 0.05) meaning that there was an effect of EIG administration on reducing blood glucose levels in rats, and there was a reduction of HbA1c but not significant. Conclusion; The combination of snakehead fish extract 300mg/kg BW and metformin 45 mg/kg BW was superior in lowering blood glucose and HbA1c levels compared to single therapy with snakehead fish extract or metformin.